How Firms Adapt Marketing and Business Strategies Amid Price Controls and Transparency-Driven Regulation in Indonesia - Syifa Faradilla Firdayanti (AIBPM Publisher, 2025)
In recent years, Indonesia has experienced a notable increase in corporate bankruptcies, especially among large firms struggling to adapt to shifting regulations and market dynamics, reflecting a growing tension between strategic agility and heightened government intervention. Under the current administration, policies such as price controls and stricter transparency requirements have pressured companies to adjust rapidly or risk decline. This study investigates how resilient Indonesian firms modify their marketing and business strategies to sustain growth under regulatory constraints. Using a quantitative approach, data were collected through surveys of senior executives in marketing, finance, and strategy from medium-to-large enterprises across highly regulated sectors, including manufacturing, consumer goods, logistics, and retail. The analysis examines the relationship between perceived regulatory pressure and key performance indicators—revenue growth, brand performance, and competitive positioning—while considering moderating factors such as industry sector and firm age. By framing the research within the context of rising bankruptcy trends, this thesis aims to identify the strategic characteristics that distinguish firms capable of surviving and growing from those that fail, thereby contributing practical insights to the fields of strategic marketing and management within Indonesia’s evolving policy landscape